Penegakan Hukum Konservasi Lingkungan di Indonesia dalam Perencanaan Pembangunan Berkelanjutan - Fatma Ulfatun Najicha (DOKTRINA: JOURNAL OF LAW, 2022)
This study discusses the importance of enforcing environmental conservation laws and their policies on the protection and management of biodiversity as the sustainable development process in Indonesia goes. This is based on the existence of potential biodiversity that is widespread in Indonesia, where this biodiversity is in dire need of management and protection. Biodiversity protection is a shared responsibility of all people on earth, so it is necessary to consider the establishment of institutional networks both regionally, nationally, and even internationally. Therefore, it is necessary to firmly enforce environmental conservation laws in order to maintain the existence of this biodiversity potential. By using a normative research method or an approach to legislation and a concept approach, this research was conducted to examine the regulation and effectiveness of environmental conservation law enforcement in Indonesia. Where even though Indonesia has had various laws and regulations related to biodiversity, their implementation is still weak and ineffective. In addition, there are still many regulations made that still do not cover the interests of all parties.